Prescribing Medications in Patients with Decompensated Liver Cirrhosis - Deepak N. Amarapurkar (International Journal of Hepatology)
Patients with decompensated liver cirrhosis have various serious complications which require multiple drugs for therapeutic or prophylactic use. Majority of the drugs are primarily metabolized and excreted by hepatobiliary system; hence, liver cell necrosis contributes to impaired drug handling in liver failure while portosystemic shunt can alter drug action in cirrhosis. Hence, in order to decide drug dosing in liver failure, 3 important factors need to be considered (1) pharmacokinetic alterations of drugs, (2) pharmacodynamic alteration of drugs, and (3) increased susceptibility of patients to adverse events particularly hepatotoxicity. Though there is no predictable test which can be used to determine drug dosage in patients with decompensated liver cirrhosis, drugs with first pass metabolism require reduction in oral dosages, for high clearance drugs both loading and maintenance dosages need adjustment, for low clearance drugs maintenance dose needs adjustment, whenever possible measuring drug level in the blood and monitoring of adverse events frequently should be done. No evidence-based guidelines exist for the use of medication in patients' with liver cirrhosis. There are hardly any prospective studies on the safety of drugs in cirrhotic patients. According to the experts opinion, most of the drugs can be used safely in patients with cirrhosis, but drug-induced hepatotoxicity may be poorly tolerated by patients with cirrhosis; hence, potential hepatotoxins should be avoided in patients with liver cirrhosis. Potentially hepatotoxic drugs may be used in patients with liver cirrhosis based on the clinical needs and when there are no alternatives available. Caveat for the prescribing medications in patients with cirrhosis the drug dosing should be individualized depending on a number of factors like nutritional status, renal function, adherence, and drug interaction. Monitoring of the liver function at frequent intervals is highly recommended.